Effects of novel flash glucose monitoring system on glycaemic control in adult patients with type 1 diabetes mellitus: protocol of a multicentre randomised controlled trial. Issue 12 (4th December 2020) - Zhou, Yongwen; Deng, Hongrong; Liu, Hongxia; Yang, Daizhi; Xu, Wen; Yao, Bin; Yan, Jinhua; Weng, Jianping
Abstract : Introduction: Optimal glycaemic control is beneficial to prevent and delay microvascular complications in patients with type 1 diabetes mellitus (T1DM). The benefits of flash glucose monitoring (FGM) have been proved among well-controlled adults with T1DM, but evidence for FGM in adults with T1DM who have suboptimal glycaemic control is limited. This study aims to evaluate the effect of FGM in suboptimally controlled adult patients with T1DM . Methods and analysis: This open-label, multicentre, randomised trial will be conducted at eight tertiary hospitals and recruit 104 adult participants (≥18 years old) with T1DM diagnosed for at least 1 year and with suboptimal glycaemic control (glycated haemoglobin (HbA1c) ranging from 7.0% to 10.0%). After a run-in period (baseline, 0–2 weeks), eligible participants will be randomised 1:1 to either use FGM or self-monitoring of blood glucose alone consequently for the next 24 weeks. At baseline, 12–14 weeks and 24–26 weeks, retrospective continuous glucose monitoring (CGM) systems will be used in both groups for device-related data collection. Biological metrics, including HbA1c, blood routine, lipid profiles, liver enzymes, questionnaires and adverse events, will be assessed at baseline, week 14 and week 26. All analyses will be conducted on the intent-to-treat population. Efficacy endpoint analyses will also be repeated on the per-protocol population. The primary outcome is the change of HbA1c from baseline to week 26. The secondary outcomes are the changes of CGM metrics, including time spent in range, time spent in target, time spent below range, time spent above range, SD, coefficient of variation, mean amplitude of glucose excursions, high or low blood glucose index, mean of daily differences, percentage of HbA1c in target (<7%), frequency of FGM use, total daily insulin dose and the scores of questionnaires including Diabetes Distress Scale, Hypoglycemia Fear Scale and European Quality of Life Scale. Ethics and dissemination: This study was approved by the Ethics Committee of the Third Affiliated Hospital of Sun Yat-sen University in January 2017. Ethical approval has been obtained at all centres. All participants will be provided with oral and written information about the trial. The study will be disseminated by peer-review publications and conference presentations. Trial registration number: NCT03522870 .